Net Modulation of Upper Ocean Thermal Structure by Typhoon Kalmaegi (2014). Issue 10 (9th October 2018) - Zhang, Han; Wu, Renhao; Chen, Dake; Liu, Xiaohui; He, Hailun; Tang, Youmin; Ke, Daoxun; Shen, Zheqi; Li, Junde; Xie, Juncheng; Tian, Di; Ming, Jie; et al.
Abstract: In situ observation of a buoys/moorings array and a model simulation were used to study the modulation of upper ocean thermal structure by Typhoon Kalmaegi in September 2014. The inertial period signals were significant after forcing of Kalmaegi, but they did not account for the net heat change. Removing the inertial period signals showed that the net thermal response biased to the right of Kalmaegi's track. Vertical mixing caused surface cooling with an inverted‐cone structure and subsurface warming with a double‐wing structure. Net upwelling converted the left wing of the subsurface warming to cooling, while net downwelling warmed the upper ocean in front and on both sides of the net upwelling zone. Horizontal advection was not as important as vertical mixing and vertical advection in modulating the thermal structure but contributed to the net outward advection of thermal anomaly in the mixed layer during the forced stage and also in the net along‐track recovery of subsurface anomaly during the relaxation stage. In general, horizontal and vertical advection modulated thermal anomalies in the upper ocean across a broader horizontal range and into the deeper ocean compared with the effect of vertical mixing. Our results indicate the need to consider both mixing and advection (rather than only mixing) when studying the effects of tropical cyclones on local ocean heat uptake and global ocean heat transport. Plain Language Summary: Tropical cyclones are strong natural phenomena occurring on the ocean. Tropical cyclones intensify ocean mixing and deepen surface mixed layer (defined as a layer with uniform temperature). In so doing, it creates cold anomaly at the surface and warm anomaly in the subsurface, which can be considered as a downward pump of warm water ( heat pump effect). The subsurface warming cannot be directly recovered by air‐sea surface interaction; it may stay in the ocean and contribute to global ocean heat transport and then influence the climate system. This work studied the upper ocean thermal response to a tropical cyclone (typhoon Kalmaegi) in September 2014. The results show that besides the surface cooling and subsurface warming, typhoon Kalmaegi also cools the subsurface by an upwelling process. Upwelling brings up cold water, and part of subsurface warming is modulated outside of the main response area and into the deeper ocean ( cold suction effect). This work indicates that the upper ocean thermal response to a tropical cyclone is more complicated than only heat pump effect. Cold suction effect needs to be taken into consideration when estimating the tropical cyclones' contribution to global ocean heat budget. Key Points: Typhoon Kalmaegi caused net surface cooling, near‐track subsurface cooling, and warming in the remaining regions Vertical mixing caused surface cold anomaly with an inverted‐cone structure and subsurface warm anomaly with a double‐wing structure Advection converted left wing of subsurface warm anomaly to cold anomaly and modulated heat anomaly to broader and deeper ocean